Teachers' Experiences in Facing the Complexity of the Independent Curriculum in the Basic Education Environment: Pengalaman Guru dalam Menghadapi Kompleksitas Kurikulum Merdeka di Lingkungan Pendidikan Dasar - Bakri, Nofri; Yawati, Yunita Sulisti; Elya, Zurtina; Demina, Demina (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
Abstract: The Independent Curriculum is a new challenge for teachers in basic education environments. In 2022/2023 schools will be able to choose the curriculum that will be used in the education unit. There are 3 curriculum options available according to school conditions. This article aims to explore teachers' experiences in dealing with the complexity of the independent curriculum that has been implemented and its impact on the learning process. Through qualitative research using in-depth interviews and observations, it was found that teachers face various challenges and opportunities in implementing the Independent Curriculum at the education unit level, especially elementary schools. Keywords: Teacher experience, complexity, independent curriculum